2022
DOI: 10.1002/admi.202200210
|View full text |Cite
|
Sign up to set email alerts
|

Atomic/Molecular Layer Deposition for Designer's Functional Metal–Organic Materials

Abstract: organic ligands act as bridges between the metal centers to form infinite 1D, 2D, or 3D structures. These materials are often referred to as coordination polymer (CP) [1] or metal-organic framework (MOF) [2] materials; the latter term is used when the metal-organic material is crystalline and highly porous. [3] The research field of CP-and MOF-type materials has grown tremendously over the last two decades. The structural and chemical diversity of these materials has served as a continuous source of scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 476 publications
(1,289 reference statements)
0
38
0
Order By: Relevance
“…Such possibility can be accessed by combining the use of organic precursors during the ALD process (such as alcohols, ROH�R being a generic organic fragment�rather than H 2 O as an oxygen source). The presence of the organic chemical residues prevents the crystallization during the growth of the hybrid inorganic−organic thin film (metalcones in the examples just mentioned 13,19 ) at low temperatures. A subsequent treatment (typically annealing, which induces the loss of most of the organic fragment) leads to the crystallization of the mineral phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such possibility can be accessed by combining the use of organic precursors during the ALD process (such as alcohols, ROH�R being a generic organic fragment�rather than H 2 O as an oxygen source). The presence of the organic chemical residues prevents the crystallization during the growth of the hybrid inorganic−organic thin film (metalcones in the examples just mentioned 13,19 ) at low temperatures. A subsequent treatment (typically annealing, which induces the loss of most of the organic fragment) leads to the crystallization of the mineral phase.…”
Section: Introductionmentioning
confidence: 99%
“…Such possibility can be accessed by combining the use of organic precursors during the ALD process (such as alcohols, ROHR being a generic organic fragmentrather than H 2 O as an oxygen source). The presence of the organic chemical residues prevents the crystallization during the growth of the hybrid inorganic–organic thin film (metalcones in the examples just mentioned , ) at low temperatures. A subsequent treatment (typically annealing, which induces the loss of most of the organic fragment) leads to the crystallization of the mineral phase. , For instance, the combination of such an organic precursor-based ALD approachwhich is called herein atomic layer deposition/molecular layer deposition (ALD/MLD)and the post-annealing step allowed to control the porosity of Al 2 O 3 thin films, as well as the crystallinity, composition, and electrochemical properties of SnO/SnO 2 , TiO 2 , and V 2 O 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid (metal–organic) materials have been accessed by gas-phase ALD as the so-called “molecular layer deposition” (MLD) generalization; however, the range of compounds accessible in MLD is quite narrow. This is related to the limited choice of molecular precursors that possess sufficient thermal stability and volatility. , ZIF-8 MOF has been obtained from a conversion of ALD-grown ZnO . Success in the direct growth of MOFs by ALD has remained limited. In the literature, it is reported that the crystallinity is obtained upon post-deposition processing, either with a thermal annealing step or an extended aging at room temperature. Gas-phase deposition methods usually compete with the limited thermal stability of MOFs.…”
Section: Introductionmentioning
confidence: 99%
“… 26 Success in the direct growth of MOFs by ALD has remained limited. 27 30 In the literature, it is reported that the crystallinity is obtained upon post-deposition processing, either with a thermal annealing step or an extended aging at room temperature. Gas-phase deposition methods usually compete with the limited thermal stability of MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Molecular layer deposition (MLD) is based on the same principles as ALD but for purely organic polymers, while the combination of the two techniques, ALD/MLD, provides an attractive route for the fabrication of intriguing metal-organic thin films for a variety of emerging application fields. [4][5][6][7][8] While the inorganic component in these hybrid materials typically forms the basis for the desired electrical, optical, magnetic or catalytic functionality, the organic component could bring e.g. mechanical flexibility, 5,9,10 additional structural/chemical tunability [11][12][13][14][15] or even unforeseen bio-or lightbased actions [16][17][18][19] for the hybrid material.…”
Section: Introductionmentioning
confidence: 99%